Configurations of democracy—empirical and methodological insights from a comparison of Singapore, Ghana, and Ireland - Osterberg-Kaufmann, Norma; Stark, Toralf; Mohamad-Klotzbach, Christoph (Frontiers in Political Science, 2024)
This article presents and proofs an alternative concept of democracy that seeks to overcome the limitations of rigid universalist, liberal-proceduralist conceptions by emphasizing the fundamental principles of democracy rather than combining them with culturally individualistic features. The approach presented here focuses on the fundamental principles of democracy. Democratic configurations assume that citizens’ political self-efficacy of the people is a potential basic principle behind any institutionalization of democratic order. Therefore, this article refers on a discussion of the theoretical implementation of self-efficacy in the three models of democracy: liberalism, republicanism and communitarianism. Ultimately, every political system must be studied by whether the established institutions serve this basic principle. The article illustrates the proposed approach through case studies of Singapore, Ghana, and Ireland. The empirical examples show how different institutional settings and their adjustments strengthen and hinder political self-efficacy. Therefore, this new bottom-up-approach of studying configurations of democracy may help to get better insights on the democraticness of political systems and other institutional settings.